2020
DOI: 10.1108/gkmc-09-2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of librarians as teachers of information literacy at a large African university

Abstract: Purpose The purpose of this study is to determine the students’ perceptions of librarians as teachers of information literacy at the North-West University in South Africa. Design/methodology/approach The study used a survey research method in which online questionnaires were used to gather data from students who would have attended information literacy classes. Findings Students found librarians to be effective teachers of information literacy, and they found the subject to be very useful. However, some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Based on this, it is evident that the members are exposed to sources of information and librarians also raise awareness of the LibGuide, which is one of the resources used to embed informative content to support teaching, learning and research needs. These findings are consistent with the study by Bangani et al (2020: 411), in which students reported that librarians were very helpful and encouraging during IL training sessions to equip them with the skills necessary to use various information sources and to cite them properly.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on this, it is evident that the members are exposed to sources of information and librarians also raise awareness of the LibGuide, which is one of the resources used to embed informative content to support teaching, learning and research needs. These findings are consistent with the study by Bangani et al (2020: 411), in which students reported that librarians were very helpful and encouraging during IL training sessions to equip them with the skills necessary to use various information sources and to cite them properly.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Wenger (2014: 142) argues that many of the information-seeking skills that students need to conduct successful research are difficult for librarians to teach due to student overreliance on search engines and the time constraints of one-shot instruction sessions; thus, PjBL is required. This is also supported by a study conducted among North-West University students evaluating librarians as teachers of IL, in which respondents expressed dissatisfaction with one-time instructions and the duration of training sessions (Bangani et al, 2020: 408). The findings of a study conducted by Syakur et al (2020) reported that this model improved student learning outcomes of English in higher education.…”
Section: Methodsmentioning
confidence: 75%